The Word universe a journey to West Africa [videorecording] - Keegan, Mark; Marley, Bob ([United States] [Studio 1605], 1995)
An American visits his African friend, who has fled with his family from their home in Liberia to the Ivory Coast. Film examines the personal costs of the civil war raging in Liberia upon the refugees.
Videorecording.
Producer/director, Mark Keegan ; music, Bob Marley ; editors Mark Keegan, Vigil Chime.
Interviews: J. Walleh Toe, Winston M. Tuhman II, Nathaniel N. "J5" Nyema, S. Othello Wesse, Jr., John Cooper.
VHS.
Keywords: Refugees -- Liberia; Refugees -- Côte d'Ivoire.; Liberia -- History -- Civil War, 1989-1996 -- Personal narratives; Liberia -- History -- Civil War, 1989-1996 -- Refugees; Liberia -- History -- Civil War, 1989-1996 -- Atrocities; Liberia -- Social conditions|y1980-.